LITERATURE REVIEW RISK FACTOR OF LOWER BACK PAIN IN OFFICE WORKERS WITH VIDEO DISPLAY TERMINAL (VDT) - Yosephin Sri Sutanti; Ruth Mary Kasan; Johannes Hudyono; Yusuf Handoko (Dinasti International Journal of Education Management And Social Science, 2022)
Lower back pain (LBP) has become the most common musculoskeletal condition in developing countries. In Indonesia, it ranges from 3-17% affected by LBP. This is also related to the use of Visual Display Terminal (VDT), because the use of VDT is also related to one's sitting position. It is also known that, LBP is the third leading cause of occupational diseases caused by using VDT. Literature reviews that are based on articles and journals customized to PICO (population, intervention, control, output). Journals were searched in medical databases through Google Scholar, JOEM, and the Cochrane Library, using the keywords "low back pain", "risk factor", "office worker" and "VDT". From 4 selected journals, it was found that gender, age, Body Mass Index (BMI), sitting duration, working period, computer use, sitting position, LBP history became a risk factor for LBP occurrence and proved to be related to LBP because it has a value of p=<0.05. Workers working with VDT who experienced significant lower back pain were found to be more numerous in female workers, workers with an age range of 40-50 years, smokers, workers who had worked in the range of 1-21 years, previous LBP history, BMI >25, using computers 4-6 hours a day, working overtime, and also work experience with computers for 6-15 years.